Preparation of ultra-high temperature SiC–TiB2 nanocomposites from a single-source polymer precursor. Issue 12 (15th August 2020) - Zhu, Chaoqun; Feng, Lukun; Xu, Binbin; Lin, Qingying; Cheng, Xiaoli; Chen, Jiangxi; He, Guomei
Abstract: SiC–TiB2 ceramic nanocomposites are valuable ultra-high temperature materials, which are rarely prepared from preceramic polymers. In this work, we synthesized SiC–TiB2 nanocomposites from a new preceramic polymer called titanium- and boron-modified polycarbosilane (TB–PCS ). The polymer structure was characterized by Fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance (NMR) spectroscopy. The structure, composition, and morphology of the resulting ceramic products were investigated by FT-IR, X-ray diffraction, and transmission electron microscopy. The elements of titanium and boron were incorporated into the preceramic polymer, and nanoscale TiB2 and β-SiC grains generated in situ were detected in the pyrolyzed ceramic products at temperatures higher than 1400 °C. The new preceramic polymer presents a novel approach to preparing SiC–TiB2 nanocomposites.